Pengaruh Gaya Hidup Terhadap Pengelolaan Keuangan Pribadi Generasi Z - M. Masrukhan; Fitria Nur Afifa; Salsa Nabila; Fatimah Az-Zahra Nurdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Quantitative methods were used in this study to determine how lifestyle impacts personal financial management. Lifestyle includes the decisions a person makes about how they live their daily lives, especially about how they spend their time and money. The process of effectively managing a person or family's income, expenses, and assets to achieve short-term and long-term financial goals is known as personal financial management. Planning, budgeting, investing, investing, and debt management are all part of this. This questionnaire was circulated and completed by 66 people. Validity, reliability, and classical assumption tests have been used to collect data. Simple linear regression analysis was also used in this research methodology. The results of this study show that lifestyle has a positive impact on personal financial management.